Bilateral Acute Iris Transillumination - Rafique, Aisha; Nazir, Noman; Zamir, Quratulain (Pakistan Armed Forces Medical Journal, 2022)
Bilateral Acute Iris Transillumination is a rare entity characterized by pigment dispersion, raised intraocular pressure and sluggish pupils. It usually follows systemic infections. A mid aged female presented with photophobia, visual blurring and ocular pain. Bilateral ocular examination revealed patchy loss of iris pigment epithelium, pupillary atrophy, and persistent mydriasis and raised intra ocular pressure. She had history of acute respiratory infection treated with oral moxifloxacin one month before onset of her ocular discomfort. Her ocular symptoms were managed with topical pressure lowering drugs and steroids which improved over a period of 6 to 9 weeks, however, pupils remained slightly dilated.